Asbestos and the anti-asbestos campaign: a review - Jargin, S.V. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
Assessment of health risks associated with asbestos is based on practical experience, when the asbestos fiber content in the air was artificially increased. Asbestos fibers enter the environment as a result of the erosion of asbestos materials and other human activities not related to the asbestos industry. When specifically searched for, fibers are often detected during autopsies. The results of many studies are more or less biased. When fibers are detected, mesothelioma or lung cancer is sometimes classified as asbestos-related, although the causal relationship remains unproven. Some studies rely on unverified anamnesis on professional or domestic contact with asbestos. Reliable data can be obtained in experiments recording the average lifespan of animals. Different types of asbestos have specific technical characteristics and are used in various fields. For example, asbestos is used in the manufacture of brake pads. Construction materials based on a mixture of cement and asbestos are distinguished by low cost and long service life. Asbestos products are also widely used as fireresistant materials. On the one hand, the refusal to use asbestos has a positive effect on the environment, but on the other hand, refusing to use it will lead to increased damage from transport and fires, and will increase the cost of construction.
Асбест және асбестке қарсы науқан: шолу
Асбест и антиасбестовая кампания: обзор
Keywords: asbestos; chrysotile; asbestos-related diseases; mesothelioma; lung cancer; amphiboles